Recurrent Tracheoesophageal Fistula - Lal, Dave R.; Oldham, Keith T. (European Journal of Pediatric Surgery, 2013)
Repair of recurrent tracheoesophageal fistulas (rTEFs) remains a technically challenging endeavor. Although considered the gold standard, open surgical repair is associated with significant morbidity and rates of recurrence. Over the last 40 years, endoscopic techniques have gained popularity and been touted as a safer first line treatment. This review complies the published articles related to endoscopic repair of rTEFs and reports the various techniques, number of interventions, and success rates. Controversy will remain as to which technique is superior until prospective, multi-institutional studies are performed.
Keywords: recurrent tracheoesophageal fistula; endoscopic treatment; open surgery; tissue adhesives; de-epithelializing agents; fistula ablation